Pelatihan Pembuatan Bahan Ajar Kreatif dengan Media Canva Bagi Guru dalam Upaya Meningkatkan Hasil Belajar Siswa MTs Al Abraar - Humaizi Humaizi; Muhammad Yusuf; T. Kasa Rullah Adha; Umaya Ramadhani Putri Nasution (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Abstract, In recent years, there have been challenges faced by MTs Al Abraar in an effort to improve student learning outcomes, especially in creating creative and innovative learning. The partners involved in this program are teachers at the Al-Abraar Tandem Hilir Private Middle School, Hamparan Perak District, where the main problem experienced by partners is the lack of knowledge in using IT in creating creative teaching materials. Therefore, the solution offered is to provide training in creating creative teaching materials to improve teachers' knowledge and skills in creating, using and optimizing the use of Canva. The location for implementing this program has been discussed with partners, namely at the Al Abraar Tandem Hilir Private Middle School located at Jln. Listrik Emplasmen Tandam Hilir I, Hamparan Perak District, Deli Serdang Regency, North Sumatra. This program consists of stages of preparation, implementation, monitoring, and evaluation. In implementing this service, the team implemented the in-house training method. In the implementation of the training, the community service team provided tutorial materials on the use of Canva which would be carried out for 2 meetings (2 meetings per material) and carried out alternately with a duration of 120 minutes each. Training activities on this were carried out on August 8-9, 2024 offline with lecture methods, direct training, discussions and questions and answers. The results of this activity can be seen that the participants of the activity can recognize and can create creative teaching material designs using Canva and its supporting features and are used in teaching. The sustainability of this program can be measured by the existence of teaching materials made using Canva.